APLIKASI TEKNIK STAND UP COMEDY DALAM PENINGKATAN PRESTASI BELAJAR MENULIS ANEKDOT - Darsono Darsono (MEDIA DIDAKTIKA, 2015)
Writing skills would not come automatically but must go through training and practice in many and regular. Based on observations made by researcher in the tenth graders-PBS SMK 1 Lamongan showed that the students' level of activity was very less to the learning that takes place in the material writing anecdotes. The low level of involvement of the student in learning the material due to write anecdotes on Curriculum 2013 was unfamiliar to students and newly recognized, thus making the results less learning take place according to what has been planned by the teacher. Teacher considered the need for innovation in learning to overcome these problems. One was through the application of methods of engineering applications standup comedy in the writing of anecdotes. From the results of learning activities that had been performed for two cycles, and based on the entire discussion and analysis could be summarized as follows: (1) The learning model using engineering applications standup comedy in writing anecdotes had a positive impact in improving student achievement marked by increased mastery learning students in each cycle, the first cycle = 75% and cycle II = 88.9%; (2) Implementation of the learning model using engineering applications standup comedy in writing anecdotes, could increase the students' motivation.